1998
DOI: 10.1210/en.139.4.1991
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cyclic Adenosine 3',5'-Monophosphate on p70 Ribosomal S6 Kinase

Abstract: cAMP exerts differential effects on mitogenic signaling pathways. In many cells, cAMP inhibits growth factor-stimulated MAPK activity and proliferation. In others, cAMP promotes growth. TSH stimulates proliferation through elevations in cAMP in thyroid follicular cells. This mitogenic pathway is dependent upon both protein kinase A and Ras, but not upon Raf-1, mitogen-activated protein kinase kinase, or mitogen-activated protein kinase. We report that TSH, acting through cAMP, activates pp70s6k and that this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 0 publications
8
39
3
Order By: Relevance
“…In our FRTL-5 cell line, forskolin alone does not stimulate DNA synthesis, in agreement with results showing that TSH alone has no effect on DNA synthesis in WRT thyroid cells (6). The cAMP/PKA-dependent pathway has been shown to activate p70-S6 kinase (S6K1) in thyroid cells (7), which is essential for cell cycle progression in many cell types. Although the activation of PKA was necessary for cell cycle progression, it has been suggested that PKA-independent mechanisms might be required in cAMP-mediated growth of thyroid cells (8,9).…”
Section: Introductionsupporting
confidence: 91%
“…In our FRTL-5 cell line, forskolin alone does not stimulate DNA synthesis, in agreement with results showing that TSH alone has no effect on DNA synthesis in WRT thyroid cells (6). The cAMP/PKA-dependent pathway has been shown to activate p70-S6 kinase (S6K1) in thyroid cells (7), which is essential for cell cycle progression in many cell types. Although the activation of PKA was necessary for cell cycle progression, it has been suggested that PKA-independent mechanisms might be required in cAMP-mediated growth of thyroid cells (8,9).…”
Section: Introductionsupporting
confidence: 91%
“…These data unequivocally show the key role of mTOR in inducing thyrocyte proliferation downstream of TSHR. The involvement of S6K1 in TSH-dependent proliferation had been previously suggested by studies in dog and rat thyrocytes (6,9), although the mechanisms of S6K1 activation downstream of TSH had not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Likely candidates to transduce these mitogenic signals include the cAMP-responsive element binding protein (CREB; ref. 5), p70S6K (6), and the small GTPase Rap1 (7). However, microinjection of Rap1 failed to induce proliferation of dog thyrocytes, showing that Rap1 alone is not sufficient to trigger thyroid cell growth (8).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of basal and stimulated p70 S6k activity in hepatocytes by glucagon is consistent with studies in other cell types in which cAMP is antiproliferative, 44,45 although stimulation of p70 S6k by agents increasing intracellular cAMP has been shown in cells in which cAMP is mitogenic. 46,47 The inhibition of interleukin-2-stimulated p70 S6k activity in T lymphocytes and smooth muscle cells by cAMP occurs at the level of PI 3-kinase. 44,45 TGF-␤ has no effect on either basal or stimulated levels of cAMP in hepatocytes, 6 and, on the basis of our results, no effect on the activity of PKB or, by inference, PI 3 kinase.…”
Section: Fig 3 Tgf-␤ and Glucagon Do Not Inhibit Egf-induced Jnk1 Omentioning
confidence: 99%